Documenting Program Outcomes of Relationship Education with Incarcerated Adults - Adler-Baeder, Francesca (Journal of human sciences and extension, 2015)
The current study examined program outcomes for an understudied population of Relationship Education (RE) participants: incarcerated men and women. In addition to relationship functioning, we examined a number of individual and parenting outcomes which had not previously been explored. In a sample of 453 adult inmates, we found improvements in (a) trust, (b) confidence in the relationship, (c) intimacy, (d) individual empowerment, (e) conflict management, (f) help-seeking attitudes, (g) self-esteem, (h) depression, (i) global life stress, (j) faulty relationship beliefs, and (k) parenting efficacy. Tests of moderation by gender and race indicated minimal differences in change patterns between groups; however, we found a significant time by gender interaction on intimacy and a time by race interaction on parenting efficacy. Implications for research and practice are presented